Impact of comorbid personality disorders on psychotherapy for post-traumatic stress disorder: systematic review and meta-analysis. Issue 1 (1st January 2021) - Snoek, Aishah; Nederstigt, Jelle; Ciharova, Marketa; Sijbrandij, Marit; Lok, Anja; Cuijpers, Pim; Thomaes, Kathleen
ABSTRACT: Background : Although personality disorders are common in PTSD patients, it remains unclear to what extent this comorbidity affects PTSD treatment outcome. Objective : This constitutes the first meta-analysis investigating whether patients with and without comorbid personality disorders can equally benefit from psychotherapy for PTSD. Method : A systematic literature search was conducted in PubMed, EMBASE, PsychINFO and Cochrane databases from inception through 31 January 2020, to identify clinical trials examining psychotherapies for PTSD in PTSD patients with and without comorbid personality disorders (PROSPERO reference CRD42020156472). Results : Of the 1830 studies identified, 12 studies reporting on 918 patients were included. Effect sizes were synthesized using a random-effects model. Patients with comorbid personality disorders did not have significantly higher baseline PTSD severity (Hedges' g = 0.23, 95%CI −0.09–0.55, p = .140), nor were at higher risk for dropout from PTSD treatment (RR = 1.19, 95%CI 0.83–1.72, p = .297). Whilst pre- to post-treatment PTSD symptom improvements were large in patients with comorbid PDs (Hedges' g = 1.31, 95%CI 0.89–1.74, p < .001) as well as in patients without comorbid PDs (Hedges' g = 1.57, 95%CI 1.08–2.07, p < .001), personality disorders were associated with a significantly smaller symptom improvement at post-treatment (Hedges' g = 0.22, 95%CI 0.05–0.38, p = .010). Conclusion : Although the presence of personality disorders does not preclude a good treatment response, patients with comorbid personality disorders might benefit less from PTSD treatment than patients without comorbid personality disorders. HIGHLIGHTS: This meta-analysis suggests that although patients with comorbid PDs do not have more severe PTSD symptoms at baseline, nor are at higher risk for dropout from PTSD treatment, they might benefit less from PTSD treatment compared to patients without comorbid PDs.